1996
DOI: 10.1128/jb.178.14.4012-4019.1996
|View full text |Cite
|
Sign up to set email alerts
|

Transcript analysis of the c-vac region and differential synthesis of the two regulatory gas vesicle proteins GvpD and GvpE in Halobacterium salinarium PHH4

Abstract: Halobacterium salinarium PHH4 synthesizes gas vesicles in the stationary growth phase by the expression of 14 gvp genes arranged in two clusters. The chromosomal gvpACNO (c-gvpACNO) gene cluster (encoding the major structural gas vesicle protein GvpA and the minor structural protein GvpC) was transcribed as three mRNA species starting at one promoter during the stationary phase of growth. The second gene cluster, c-gvpDEFGHIJKLM, was transcribed during all stages of growth as a relatively unstable, single mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 32 publications
2
38
0
3
Order By: Relevance
“…7 Binding studies using TFB His or GvpH His and cGvpE. Western analyses were performed with proteins derived from the Ni-NTA aYnity chromatography using an antiserum raised against cGvpE (Krüger and Pfeifer 1996). Ni-NTA matrices loaded with 400 g of the TFB His protein were incubated with 2 mg of soluble proteins of Hfx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Binding studies using TFB His or GvpH His and cGvpE. Western analyses were performed with proteins derived from the Ni-NTA aYnity chromatography using an antiserum raised against cGvpE (Krüger and Pfeifer 1996). Ni-NTA matrices loaded with 400 g of the TFB His protein were incubated with 2 mg of soluble proteins of Hfx.…”
Section: Discussionmentioning
confidence: 99%
“…The faint band at 66 kDa is due to PitA, an endogenous, multiple histidine residues containing protein that always co-puriWes on Ni-NTA matrices (Bab-Dinitz et al 2006). Western analyses using an antiserum raised against cGvpE (Krüger and Pfeifer 1996) detected GvpE in all samples derived from TFB His matrices (Fig. 7, lane 2 each).…”
Section: Interaction Of Tfb and Gvpementioning
confidence: 95%
“…the c-gvpDEFGHIJKLM operon, is also transcribed in this strain. However, only cGvpD involved in the repression of gas vesicle formation is detectable, whereas the transcriptional activator cGvpE required for the activation of the P cA promoter is absent (Krüger and Pfeifer 1996). The presence of the other cGvp proteins encoded by this operon has not yet been determined.…”
Section: Gas Vesicle Gene Clusters and Minimal Vac Regionmentioning
confidence: 98%
“…GvpE is a transcriptional activator, whereas GvpD has a role in the repression of gas vesicle formation (Offner and Pfeifer 1995). Most of the gvp promoters are induced by GvpE (Krüger and Pfeifer 1996;Zimmermann and Pfeifer 2003;Hofacker et al 2004). Archaeal promoters consist of a TATA-box centred around position-28 upstream of the transcriptional start site, and the transcription initiation factor TFB, the TATA-box binding protein TBP and a multicomponent RNA polymerase (RNAP) related to the eukaryotic RNAP II are required for transcription initiation (Bell and Jackson 1998).…”
Section: The Regulatory Proteins Gvpd and Gvpementioning
confidence: 99%
“…Such transformation experiments showed that (i) the entire p-vac region (construct M-O) leads to gas vesicle formation in H. volcanii (10), and (ii) the p-gvpACNO (A-O) and p-gvpDEF GHIJKLM (D-M) gene clusters present on different vector constructs (or A-O/F-M ϭ ⌬DE) allow the formation of spindle-shaped gas vesicles in H. volcanii transformants (28). The GvpD and GvpE proteins are involved in the regulation of gas vesicle formation: GvpE is a transcriptional activator required for gvpA promoter activity, whereas GvpD is involved in the repression of gas vesicle formation (11,23,24,36).…”
mentioning
confidence: 99%